Forestalling Bullying in Primary and Secondary Schools in Spain - Elia Saneleuterio; Rocío López-; Teresa Fernández-Ulloa (Athens Institute for Education and Research, 2023)
Bullying refers to degrading actions, recurring and prolonged, exerted by minors on an equal. Physical or virtual assaults and insults, rejections or intimidations that hinder the victims' school activity and cause them to feel continually threatened are examples of bullying and cyberbullying, which have serious repercussions, not only on the emotional well-being and academic performance, but also on physical and mental health. It is necessary to build a citizenship engaged to education (Global Citizenship Education) to prevent bullying, and to work in other Sustainable Development Goals (SDGs). The solutions must involve families and teachers, particularly in the context of regulated education, where participation can be promoted in a more planned and controlled way. Expert approaches insist on the relevance of the school to prevent aggression and discrimination through critical and reflective attitudes towards the violence that surrounds these situations. It is about teaching students to reject them ab initio as inappropriate. The aim of this paper is to identify the characteristics of the interventions aimed at the prevention and detection of physical and psychological violence among school children in various settings and populations, specifically in Spain, as well as their results and controversial aspects.